EFFECT OF NEONATAL CARE TRAINING WITH HUSBAND’S SUPPORT IN CARING NEONATUS IN YOGYAKARTA - Nunuk Sri Purwanti; Ana Ratnawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Background: Neonatal birth is a n even t that awaited by mother dan husband. Care for neonatus is a complex task, giving physical needs and comfort for neonatus and mother, especially for the husband that first time having child. Husband is the closest person to the mother and neonatus and is a source of support to the mother such as informational support, emotional, instrumental, and awarded support. Neonatal care training will enhance of husband ability to take care of neonatus so that the husband can give support to the mother in caring neonatus. This study to determine the effect  of  neonatal  care  training  in  the  husban’s  support  to  caring  neonatus  in  Yogyakarta  city.  Design:  Quasi experimental research with pre-post test method with control group design. Statistical test using Chi-Square. Research location was in Public Health Center Mergangsan and Public Health Center Tegalrejo Yogyakarta. Result:  There was any effect of neonatal care training with husband’s support in caring neonatus both intervention groups and control groups. Sub variables for emotional and instrumental support in intervention group obtained p value <0,05 (p<0,05), sub  variables  for  informational  support  in  intevention  groups  was  p value  >0,005  (p>0,005),award  support  in intevention and control group get p value >0,000 (p>0,000). Neonatal care training for the husband provide husband’s understanding about the needs of neonatus and the importance of husband’s assistance in neonatus care. This training equips the husband to demonstrate neonatal care which is very useful to develop the ability to be a parent. Conclution: Neonatal care training for husband can improve husband’s support for neonatus caring in Yogyakarta.